Health toxicology studies of the new fungicide product in laboratory animals - T.M. Epishina (Disinfection affairs, 2026)
Presentation at the scientific-practical conference with international participation «Perspectives of disinfectology. Disinfection measures in emergency situations and in the territories of natural foci of infectious diseases» (September 22-23, 2026, Moscow)